The Use of Growth Mattress and Stunting Early Detection in Toddlers Aged 3-24 Month - Iswati, Retno Setyo; Tri Mardiyanti; Asworoningrum Yulindahwati (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Indonesia is the third Southeast Asia country that has the highest prevalence of stunting toddler. Stunting is a chronic malnutrition condition that can start within the first thousand days of life and detectable up to two years of age by height. However, the measurement of the toddler's height can be influenced by the skills of Posyandu cadres using existing tools, so that the growth mattress is launched which is easier and faster to use detect stunting. The purpose of this study was to determine the effectiveness of using growth mattress for stunting early detection in toddlers aged 3-24 months. This research is a descriptive study with a cross sectional approach which is carried out at Posyandu of Siwalankerto Community Health Center working area. Respondents involved in this study were 42 toddlers aged 3-24 months and 54.8% of them were male. Data were obtained through questionnaires and observation sheets which were filled in by Posyandu cadres independently. The results showed that the effectiveness of using growth mattress was in the range of 80.9% and could detect the presence of stunting by 7.2%. The conclusion of this study is that the use of growth mattress as a medium for early detection of stunting is mostly effective